Research Funding Mechanisms and Biomedical Research Outputs1. Issue 2 (8th March 2016) - Clark, Julian; Hirsch, Gabrielle; Jensen, Paul H.; Webster, Elizabeth
Abstract : We use scientist‐level panel data in order to estimate the effect which the number, type and source of research grants has on subsequent commercial contracts, publications and patent outputs. In so doing, we control for time‐invariant factors including individual researcher preferences, the nature of the work and the business model of the researcher's laboratory. We find that, whereas Fellowships and Project or program grants had a positive effect on whether the scientist subsequently signed a commercial contract, Equipment and Development grants had the largest impact per grant. Finally, we find that International grants were negatively associated with the number of commercial contracts signed. The data were drawn from 488 biomedical researchers at the Walter and Eliza Hall Institute over the period 2009–2012.